Psychosocial hazard in medical residents at RSUP Dr. Sardjito - Praditia, Irsa Gusninda; Hasanbasri, Mubasysyir; Effendy, Christantie (BKM Public Health and Community Medicine, 2021)
Purpose: This study aims to identify psychosocial hazards by examining the history of physical and non-physical violence, as well as the concerns experienced by residents enrolled in the specialist medical education program at Dr. Sardjito General Hospital. Methods: This research employs a descriptive-analytical design using a cross-sectional approach, in which data are collected at a single point in time. The sampling technique used is proportional stratified random sampling, where the sample is drawn in proportion to the size of each stratum within the population. Results: The majority of respondents were over 30 years old (56.03%), male (58.87%), and held a bachelor's degree (87.94%). The most commonly reported psychosocial hazard among respondents at Dr. Sardjito General Hospital was verbal non-physical violence. A significant relationship was found between demographic characteristics—specifically age—and the history of physical violence among specialist medical education students. Additionally, a relationship was observed between work shift patterns and the history of non-physical violence. Furthermore, non-physical violence was found to be associated with anxiety among the specialist medical education students at Dr. Sardjito General Hospital. Conclusion: Health organizations must establish and prioritize policies against workplace violence through educational training programs and safety protocols.